The Change of Analysis Fish Farmers Mindset of Catfish Cultivation in the Village Hangtuah of Perhentian Raja District of Kampar Regency Riau Province - Rosdiana M Manurung; Kusai '; Zulkarnaini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in December 2015 in the Village Hangtuah Perhentian Raja District at Kampar Regency in Riau Province. It’s was aimed to determine the fish farmer characteristics, change of mindset and relationship characteristics with mindset of fish farmers. The method of this study used a survey method. Total population of the fish hatchery catfish as many as 330 people composed of six groups and the rest of private business. Responden taken in this research as 33 people. Respondents were taken several group of hatchery catfish.Based on the result of the research characteristics fish farmer are productive age, low education, little family member, low working time, low income, low food consumption and size of pond. The change of fish farmer mindset significantly from the growth phase to the development phase. The significant changes are the indicators of the respondents in the group activities the level of adoption of technology and education. The significant relationship of characteristic with mindset that views on each indicator mindset in fish farming activities are: aged with the activities of respondents in the group, adoption level of technology, working time with the activities of respondents in the group, adoption level of technology, the orientation of education children, a business orientation, and income with technology adoption. Thus, it can be said that the characteristics influence the mindset of fish farmers in the conduct of its business.Keyword: Mindset, Catfish, Desa Hangtuah